Thiamin and riboflavin retention in ground beef patties pasteurized by electron beam - K.A. Hachmeister; Donald H. Kropf; V.S. Gill; Melvin C. Hunt; R.J. Kaye; James L. Marsden; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 2000)
This research focused on the effects of an electron beam irradiation treatment with the Repetitive High Energy Pulsed Power (PHEPP) accelerator at Sandia National Laboratories. Test variables included irradiation/storage temperatures (30 or 0°F), packaging environments (aerobic or nitrogen-flushed), and irradiation dose (0, 1.5, or 3.0 kGy). Ground beef patties formulated to a target fat level of 20% were packaged in barrier film under nitrogen (ca = 400 ppm residual oxygen) or sealed in aerobic packages (no vacuum), stored, and irradiated chilled or frozen. Thiamin and riboflavin levels were not affected (P>.05) by irradiation dose. Thiamin content of irradiated patties was greater for frozen vs. chilled and for nitrogenpackaged vs. aerobically packaged product. Riboflavin content was greater in frozen patties that were nitrogen packaged. Electron beam pasteurization by this method did not affect thiamin or riboflavin concentration of treated ground beef patties.
Keywords: Cattlemen& #x27; s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Ground beef; Electron beam; Thiamin; Riboflavin